The impact of culture on tourism. - Richards, Greg.; Organisation for Economic Co-operation and Development (Paris : OECD, 2009)
This publication examines the growing relationship between tourism and culture, and the way in which they have together become major drivers of destination attractiveness and competitiveness. Based on recent case studies that illustrate the different facets of the relationship between tourism, culture and regional attractiveness, and the policy interventions which can be taken to enhance the relationship, this publication shows how a strong link between tourism and culture can be fostered to help places become more attractive to tourists, as well as increasing their competitiveness as locations which to live, visit, work and invest.--Publisher's description.
Pt. 1. Increasing the attractiveness of destinations through cultural resources. Introduction -- Roles and impact of culture and tourism on attractiveness -- Policies and programmes for culture and tourism -- Conclusions, policy implications and long-term challenges -- pt. 2. Case studies from five OECD members. Introduction -- The Port Arthur historic site, Australia -- Temple Stay Programme, Republic of Korea -- State of Michoacán, Mexico -- The industrial monuments of Route of the Silesian Voivodeship, Poland.
"Greg Richards ... drafted the core of the publication"--P. [3].
Includes bibliographical references.
https://www.oecd.org/cfe/tourism/theimpactofcultureontourism.htm
boek
Keywords: Culture; Heritage tourism; Tourism